Rethinking the Role of Affect in Risk Judgment: What We Have Learned From COVID-19 During the First Week of Quarantine in Italy - Barattucci, Massimiliano; Chirico, Alice; Kuvačić, Goran; De Giorgio, Andrea (Frontiers in Psychology, 2020)
Due to COVID-19 spreading in Italy, on 11th March the Prime Minister of Italy declared the lockdown and imposed severe restrictive measures impacting citizens’ freedom at several levels. People were required to stay at home and go out only to satisfy basic needs. Several risk models have postulated a link among online searching behavior, affect, anxiety, and complaints by individuals towards Government restrictions (GR), which emerged as also related to an increased perception of knowledge towards risk. However, to date, no study has addressed how these key risk-related aspects (i.e., affect, anxiety, perceived knowledge on risk, and risk dimensions) can act jointly to orient online health information-seeking behavior, and people’s complaints towards GR imposed during the lockdown. This study investigated mechanisms underlying online health information-seeking behavior and people’s complaints towards Government’s restrictions during a COVID-19 emergency in the Italian population. Drawing from the Health Belief Model (HBM), which postulates a link between sociodemographic variables, risk and affect dimensions in an emergency, we assumed risk factors as predictors of affect and anxiety, which, in turn, were posited as mediators between risk dimensions, online health information-seeking behavior, and complaints towards GR. 1,031 participants were involved during the first week of the quarantine (11th to 18th March) and completed an online survey composed by i) an adapted version of Italian Risk Perception Questionnaire; ii) the Italian Positive (PA) and Negative Affect (NA) Schedule (PANAS-10); iii) the State Anxiety Scale (STAI-Y1); iv) ad hoc Personal knowledge measure about novel coronavirus; v) ad hoc item measuring Information search behavior regarding the novel coronavirus; vi) ad hoc measure of the complain regarding GR; vii) Socio-demographic questions. General Linear Models and Structural Equation Modeling (SEM) were carried out to test the model. Socio-demographic and cognitive factors predicted participants’ affect and anxiety, which, in turn, motivated and fully mediated both information search behavior and complain towards GR. This research can offer useful suggestions for policy-makers during the COVID-19 emergency, and it advanced the knowledge on the risk-emotion link in emergency situations.